The risks of nuclear disaster and its impact on housing prices - Michihito Ando; Matz Dahlberg; Gustav Engström (Uppsala University, Department of Economics, 2017)
Using a data set on housing sales transactions we explore the potential effect of the Fukushima disaster on housing prices in Sweden. In contrast to most earlier findings in other countries we do not find any disproportionate effect from the Fukushima disaster on housing prices in vicinity of nuclear power plants in Sweden.
urn:nbn:se:uu:diva-315266
Keywords: Q51; Q53; R21; 330; Fukushima; Nuclear accident; housing price; difference-indifferences